Cultivating Knowledge: T. H. Pardo de Tavera and Philippine Medicinal Flora - Planta, Ma. Mercedes G. (The Archive; Vol 4 No 1–2 (2023): Regular Issue Vol. 4, Nos. 1–2, 2024)
Trinidad Hermenegildo José María Juan Francisco Pardo de Tavera y Gorricho (1857–1925), a distinguished Filipino doctor and language scholar, was the Philippines’ foremost intellectual from the late nineteenth to the early twentieth century. He assumed the inaugural chairmanship of the Department of Linguistics at the University of the Philippines Diliman, established on August 28, 1922. His timeless legacy is intricately woven into Filipino intellectual history, particularly through his scholarly pursuits, including groundbreaking research on Philippine medicinal plants. In his 1892 masterpiece, Plantas medicinales de Filipinas  [Medicinal plants of the Philippines], Pardo de Tavera not only conscientiously documented Filipino healing practices but also affirmed the Philippines’ distinctive role in the global scientific community. As contemporary global interest increasingly focus on local medicinal knowledge, Pardo de Tavera’s work stands as a timeless bridge connecting the past to the future. It sheds light on the brilliance of Filipino intellect and underscores the enduring relevance of local healing knowledge, emphasizing its significance in the ongoing discourse on traditional medicine.